2008
DOI: 10.1093/jxb/ern110
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern and activity of six glutelin gene promoters in transgenic rice

Abstract: The shortage of strong endosperm-specific expression promoters for driving the expression of recombinant protein genes in cereal endosperm is a major limitation in obtaining the required level and pattern of expression. Six promoters of seed storage glutelin genes (GluA-1, GluA-2, GluA-3, GluB-3, GluB-5, and GluC) were isolated from rice (Oryza sativa L.) genomic DNA by PCR. Their spatial and temporal expression patterns and expression potential in stable transgenic rice plants were examined with β-glucuronida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 45 publications
7
73
1
Order By: Relevance
“…At first thought, the glutelin GT1 (GluA-2) promoter utilized in TRS transgenic plants might be responsible for the regional distribution of the three SBEs, as the activity of this promoter is stronger in the outer portion but much weaker in the inner part of the endosperm (Qu et al, 2008). This resulted in the three SBE isoforms being more severely inhibited in the outer portion of the endosperm but less inhibited in the inner region.…”
Section: Why Do Regional Distributions Of Three Sbes Exist In a Singlmentioning
confidence: 99%
“…At first thought, the glutelin GT1 (GluA-2) promoter utilized in TRS transgenic plants might be responsible for the regional distribution of the three SBEs, as the activity of this promoter is stronger in the outer portion but much weaker in the inner part of the endosperm (Qu et al, 2008). This resulted in the three SBE isoforms being more severely inhibited in the outer portion of the endosperm but less inhibited in the inner region.…”
Section: Why Do Regional Distributions Of Three Sbes Exist In a Singlmentioning
confidence: 99%
“…These included the 2300 element (also present in the Ara h 2.02 promoter) that moreover quantitatively regulates prolamin expression, an endosperm protein in cereals (Colot et al, 1987). Qu et al (2008) found prolamin and endospermspecific motifs in all but one rice glutelin gene promoter which controlled seed specific expression. Our results for reporter gene expression in peanut under the control of the Ara h 2 promoter largely conform with the results obtained by Kang et al (2007b) who showed that Ara h 2 polypeptides were abundant in mature seeds and diminished after germination during seedling growth.…”
Section: Discussionmentioning
confidence: 99%
“…Nine genes (MtTsms5,14,27,32,33,34,43,49, and 51) were found to be expressed at low levels across all tissues. The expression profiles of these genes diverged, implying that they contribute to functional maintenance through regulatory subfunctionalization or neofunctionalization (Qu et al, 2008). MtTsms11 and MtTsms25 were highly expressed in root tissue, while MtTsms19 and MtTsms56 were highly expressed in stem tissue.…”
Section: Expression Profiles Of Tsms Related Genes In M Truncatulamentioning
confidence: 99%
“…It therefore serves as a central model system for translational genomics based studies in plants (Town et al, 2006). Although many studies have specifically studied MS in A. thaliana, Brassica oleracea, and Oryza sativa (Honys and Twell, 2003;Qu et al, 2008;Ji et al, 2011;Zhang and Zhang, 2014), few studies have assessed MS in forage plants. In this study, we attempted to identify tapetum specific male sterility (TSMS) related genes in M. truncatula, via comparisons with A. thaliana, as a source of genomic information.…”
Section: Introductionmentioning
confidence: 99%